Penerapan Pasal 49 Ayat 1 Kuhp Dalam Tindak Pidana Penganiayaan (Studi Putusan No.32/Pid.B/2021/PN DGL) - Faathir Fedayan; Reimon Supusepa; Judy Marria Saimima (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Perpetrators of persecution should be subject to punishment as stipulated in the criminal law code, Article 351 Paragraph 1 of the Criminal Code. The defendant abused the victim, the torture was carried out in a forced defense because he felt his safety was threatened.Purposes of the Research: So it raises the problem of how to apply noodweer in Article 49 Paragraph 1 of the Criminal Code as a reason for abolishing the crime? What are the juridical consequences in the judge's consideration of the forced defense of the crime of persecution.The purpose of the study is to find out the application of noodweer in Article 49 Paragraph 1 of the Criminal Code as the reason for the abolition of the crime. To find out the juridical consequences in the judge's consideration of the forced defense of the criminal act of persecutionMethods of the Research: The problem approach used is the conceptual approach, statutory approach and case approach. The legal materials used are primary legal materials and secondary legal materials. Collection of legal materials using literature and then analyzed using quantitative analysis methods.Results of the Research: Based on the results of the research and discussion that the application of noodweer when viewed from the cases taken by the author has been implemented properly and is used as one of the reasons for abolishing a crime, where the reason is a justification but not a reason that justifies the actions of the perpetrator who violated the law, but rather someone is forced to commit an act punishment can be forgiven because there was a violation of law that preceded the act. However, not all actions that are considered as self-defense can be accepted by criminal law as a reason for criminal abolition. Because an act in the noodweer context must comply with the elements specified in Article 49 Paragraph 1 of the Criminal Code. The defense outside the elements specified in Article 49 Paragraph 1 of the Criminal Code is still possible for the offender to be subject to a criminal sentence. That there are no legal consequences for the perpetrators who are considered to have fulfilled the elements in Article 49 Paragraph 1 of the Criminal Code which says: